The World War II in the Socio-Political and Historical Discourse in the Donbas (1985–2014) - Tytarenko, Oksana (Narzędzia wojny, 2023)
The article examines the peculiarities of the reflection of the events of the Second World War in the socio-political and historical discourse in the Donbas during the „perestroika” period in the USSR and in the conditions of Ukrainian independence. The deideologization of public life, the emergence of new topics of historical studies, the access to archival sources, which were not available before, have caused significant changes in the perception of the topic of the war. These transformations were reflected in historical research, education, in the memorialization of events and participants of the war, which had previously received insufficient attention. The most actively researched topics during this period were: the everyday life in the region under the Nazi occupation, the activity of the Soviet and nationalist underground, the military campaigns on the territory of Donbas in 1941–1943. Particular attention is given to the activities of the „Book of Memory” of Ukraine, which highlighted the cost of the war and allowed hundreds of thousands of families to find information about the fate and place of burial of their relatives who died during the war. At the same time, the politicization of historical topics by different political actors greatly influenced the public mood and contributed to the escalation of the conflict in Donbas in 2014.